A WSQ-based flipped learning approach to improving students' dance performance through reflection and effort promotion. Issue 2 (4th February 2022) - Hsia, Lu-Ho; Hwang, Gwo-Jen; Lin, Chi-Jen
ABSTRACT: Flipped learning has received significant emphasis in recent years. Through this approach, students' self-learning ability can be cultivated and the time for in-class practice and teachers' and students' interaction are increased. In the past, there has been much research confirming its benefits in learning performance. Meanwhile, some studies have also pointed out that with proper educational strategies, students can be guided to have better learning engagement and higher-order thinking, which could improve their learning performance. In this study, a WSQ (Watch-Summary-Question)-based flipped learning approach was implemented in a dance course. Moreover, an experiment was conducted to investigate the impacts of the proposed approach. The participants were 173 college students from 2 classes, which were assigned to learn with the WSQ-based flipped learning approach and the conventional flipped learning approach, respectively. From the 12-week experiment, it was found that the WSQ-based flipped learning approach effectively promoted the students' dance performance and guided them to make more reflections. Furthermore, the proposed approach also engaged the students in making more efforts to think and to perfect their dance techniques.